2016
DOI: 10.3109/13880209.2016.1138970
|View full text |Cite
|
Sign up to set email alerts
|

Landolphia owariensisleaf extracts reduce parasitemia inPlasmodium berghei-infected mice

Abstract: Context Landolphia owariensis P. Beauv. (Apocyanaceae) leaf is used in southeast Nigeria to treat malaria. Objective This study evaluated the antiplasmodial activity of L. owariensis leaf extract and fractions, also the phytoconstituents were standardized and analyzed. Methods The effects of daily, oral administrations of 200, 400 and 800 mg/kg of L. owariensis leaf extract (LOE), its hexane (LOHF), ethyl acetate (LOEF) and methanol (LOMF) fractions on early, established and residual infections in Plasmodium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The result from this study agrees with a previous study on the methanol extract of the plant leaves which were found to contain alkaloids, flavonoids, saponins, tannins, and steroids. 17 Similar phytochemical constituents were also found in another study with a yield of 17.80 % however obtained from the methanol leaf extract. 10 The slight differences in the phytochemical constituents found in the present study as compared to previous studies may be due to differences in the soil quality and composition and also climatic conditions in the different geographical locations where the plant materials used were collected from.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The result from this study agrees with a previous study on the methanol extract of the plant leaves which were found to contain alkaloids, flavonoids, saponins, tannins, and steroids. 17 Similar phytochemical constituents were also found in another study with a yield of 17.80 % however obtained from the methanol leaf extract. 10 The slight differences in the phytochemical constituents found in the present study as compared to previous studies may be due to differences in the soil quality and composition and also climatic conditions in the different geographical locations where the plant materials used were collected from.…”
Section: Resultssupporting
confidence: 80%
“…For example, the acute toxicity of the dried liana bark of the plant was evaluated in Wistar rats and the LD50 was found to be above 5,000 mg/Kg. 29 The methanol leaf extract of the plant was similarly found to have an LD50 of greater than 5,000 mg/Kg 17 while the aqueous leaf extract of the plant was found to © 2023 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License have an LD50 of 3370 mg/Kg.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common feature motivating the selection of plants to test for antiplasmodial activity is traditional knowledge of use for malaria, for example ( Andrade-Neto et al., 2003 ; Bourdy et al., 2004 ; Bertania et al., 2005 ; Ramalhete et al., 2008 ; Ezike et al., 2016 ; Taek et al., 2021 ). We found that 48% of labelled species are traditionally used for malaria while only 1% of species in the underlying population are traditionally used for malaria.…”
Section: Resultsmentioning
confidence: 99%
“…Screening of chemical composition of medicinal plants revealed that they contain different bioactive compounds which include saponins, tannins, and alkaloids [ 19 ]. The main functional classes of phytochemicals with therapeutic potential include antioxidants, anticancer agents, immunity-potentiating agents, detoxifying agents, and neuropharmacological agents [ 17 ].…”
Section: Phytochemical Constituents Of Medicinal Plantsmentioning
confidence: 99%